A DFT based study of structural, electrical and vibrational properties of LiFeAs – A pnictide superconductor - Vora, Aditya M (BIBECHANA, 2025)
By the uses of ultrasoft pseudopotential and the generalized gradient approximation (GGA), we have looked at the structural, electrical and vibrational characteristics of the LiFeAs pnictide superconductor in the present work. There is a strong correlation between phonons and superconductivity, which is the major root of the superconductivity of iron pnictide superconductors. The superconducting characteristics of materials can be predicted using phonon properties. According to studies using density functional theory (DFT), LiFeAs exhibits its metallic nature in the overlaying bands close to the Fermi level. The dynamical stability is supported by positive frequencies in the phonon dispersion curves.